Airway Management of Suspected Traumatic Brain Injury Patients in the Emergency Room - Maurya, Indubala; Maurya, Ved Prakash; Mishra, Rakesh; Moscote-Salazar, Luis Rafael; Janjua, Tariq; Yunus, Mohd; Agrawal, Amit (Indian Journal of Neurotrauma, 2023)
The patients of trauma offers a special challenge because of the associated head injury, maxillofacial, neck and spine injuries, which puts the airway at imminent risk. The response time for the emergency team to initiate the airway management determines the outcome of the individual undergoing treatment. A judious implementatin of triage and Advanced Trauma Life Suport (ATLS) guidelines are helpful in the allocation of resources in airway management of trauma patients. One must not get distracted with the severity of other organ systems because cerebral tissue permits a low threshold to the hypoxic insults. Adequate preparedness and a team effort result in better airway management and improved outcomes in trauma patients with variable hemodynamic response to resuscitation. All possible efforts must be made to secure a definitive airway (if required) and should be verified clinically as well as with the available adjuncts. The success of a trauma team depends on the familiarity to the airways devices and their discrete application in various situations.
Keywords: airway management; trauma; emergency; intubation; ventilation; oxygenation